FEATURES INFLUENCE OF RISK FACTORS ON TREATMENT OUTCOME IN YOUNG PATIENTS WITH ACUTE CORONARY SYNDROME WITH ST SEGMENT ELEVATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The influence of risk factors on the outcome of treatment of patients with acute coronary syndrome with ST elevation (STEMI), the frequency and timing of streptokinase thrombolysis 1.5 million IU was analyzed. A retrospective study of the case histories of patients with STEMI for 2017-2019, who were urgently delivered by ambulance teams to the Samarkand branch of the Republican scientific center for emergency medical care, to the cardio reanimation Department for TLT with streptokinase 1.5 million IU.